2015
DOI: 10.1088/1674-1056/24/11/110302
|View full text |Cite
|
Sign up to set email alerts
|

Monogamous nature of symmetricN-qubit states of the W class: Concurrence and negativity tangle

Abstract: Using Majorana representation of symmetric N -qubit pure states, we have examined the monogamous nature of the family of states with two-distinct spinors, the W-class of states. We have evaluated the N -concurrence tangle and showed that all the states in this family have vanishing concurrence tangle. The negativity tangle for the W-class of states is shown to be non-zero illustrating the fact that concurrence tangle underestimates the residual entanglement in a pure N -qubit state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 43 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…We have noticed that the negativity tangle ξ N is non-zero for all values of N ≥ 3 [39]. This feature is seen in Fig.…”
Section: A Concurrence-tanglementioning
confidence: 62%
See 2 more Smart Citations
“…We have noticed that the negativity tangle ξ N is non-zero for all values of N ≥ 3 [39]. This feature is seen in Fig.…”
Section: A Concurrence-tanglementioning
confidence: 62%
“…It was also shown that different measures of entanglement give rise to different quantifications of residual entanglement. While it is shown that W-class of states have vanishing concurrence-tangle [1], they are shown to have non-zero negativity tangle [9,39]. It thus becomes important to choose a suitable measure of entanglement for quantifying residual entanglement and evaluating the tangle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26], the CoA of an n-qubit pure state satisfies a polygamy inequality of entanglement, and here we present a monogamy relation with respect to CoA for PCS states. Note that according to inequality (24), we can give a lower bound of CoA for the reduced density matrices of a PCS state. Next we give an example.…”
Section: -3mentioning
confidence: 99%
“…Then it may be important to investigate the monogamy of these two classes of states. Recently, Geetha et al analyzed the monogamous nature for the W class of symmetric N-qubit states in terms of the squared negativity and concurrence and presented that for these states, the concurrence tangle is zero, while the negativity tangle is non-zero, [24] the authors in Ref. [25] showed the generalized monogamy for the generalized Wclass multiqubit states.…”
Section: Introductionmentioning
confidence: 99%